Exploring the impact of social media influencer qualities, in-game advertisements, and app store optimization on the intent of undergraduate students to download mobile games while being moderated by wi-fi restrictions - Kaw, Hannalyn N. (Animo Repository, 2023)
Mobile gaming has been on the rise in recent years as it has become accessible to many consumers today. In the Philippines, around 60% of Filipinos play games on a regular basis. The topic is relevant because the industry is rapidly expanding, the study aims to find out “What is the influence of social media influencer qualities, in-game advertisements, and app store optimization towards the Intent of ID 120 undergraduate students from the College of Business at the De La Salle University - Manila to download mobile games while being moderated by their Wi-Fi restrictions?” The study has identified the independent variable to be Social Media Influencer Qualities, In-game Advertisements, and App Store Optimization. The dependent variable on the other hand is identified to be the Download Intention. Lastly, the moderating variable is Wi-Fi Restriction. The study conducted surveys and interviews to gather a qualitative and quantitative perspective on the topic. The survey targeted ID 120 undergraduate students of De La Salle University - Manila taking up any course from RVR-COB. While the interviews consisted of two different groups of interviewees. The first are from the same demographic as those who answered the survey and the second group consisted of people who are experts in the field such as professional gamers. The main method used to analyze the relationship between all the variables is Structural Equation Modeling (SEM) which consists of the following steps: Exploratory Factor Analysis, Confirmatory Factor Analysis, and running the SEM analysis. After conducting the statistical analysis, it was concluded that the relationship between Social Media Influencer Qualities and App Store Optimization with Download Intention both have a significant and positive relationship while In-game Advertisements does not have a significant relationship with Download Intention. Furthermore, Wi-Fi Restrictions is found to have a significant moderating effect on Social Media Influencer Qualities and App Store Optimization. It does not have a significant moderating effect on In-game advertisements. However, after conducting the post-hoc test, it was concluded that Wi-Fi Restrictions is not a suitable moderator for the study. Keywords: Social Media Influencer Qualities, In-game Advertisements, App Store Optimization, Download Intention, Wi-Fi Restriction, Mobile Games, Marketing, Gaming Industry, Structural Equation Modeling